Sanchar Kranti Yojana : An accelerator Program to connect Rural Sector to IT/Telecom sector with reference to Chhattisgarh State - Upadhyay, Gouri (International Journal of Computer Sciences and Engineering, 2025)
The Chhattisgarh state government has launched a new scheme in the state to fascilitate people with Smartphone. To remove the digital inequality among the inhabitants, the state government has decided to disrtibute Smartphone among the citizens of the state for free. The scheme namely Sanchar Kranti Yojna (SKY) is been implemented in august-september 2018. A new committee is formed by Chief Secretary to implement this SKY scheme across the state. The main objective of the scheme is to connect rural people through internet and also to encourage people to go cashless, make digital payments and also receive payments through net transfer. In this paper, the SKY scheme is focused which is recently launched with its positive and negative impact on people from rural area. This paper discusses the motivation, working, specification and achievements of the SKY scheme.